Pendampingan Scale Up Usaha Bagi Ibu-Ibu Keluarga Penerima Manfaat Program Keluarga Harapan Kecamatan Telanaipura Kota Jambi - Rike Setiawati; Besse Wediawati; Shofia Amin; Syahmardi Yacob; Rista Aldilla Syafri (Studium: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service program aims to provide business assistance to mothers of families who are beneficiaries of the Family Hope Program (FHP) in Telanai Pura District, Jambi City. This mentoring method is carried out in the form of participatory training regarding MSME Scale Up and Initiation of Joint Business Groups (JBG) from several similar businesses that they are currently doing. By providing this assistance, it can help the community, especially FHP beneficiary families, in overcoming problems related to business development, business feasibility and business plans that continue to grow. The material provided includes training on how to quickly scale up a business, strengthening creative thinking and innovation in running a business so that the problems and obstacles encountered can become experience in improving business management. The next material is understanding business feasibility and increasing JBG activities. This community service program as a whole lasts for eight months starting from the preparatory stage to the final report submission stage. The output of this program is the knowledge of the FHP beneficiary family community to scale up the business being run, and being able to assess business feasibility Keywords: Scale Up, Business Feasibility Assessment, Beneficiary Families FHP